Peran Motivasi Belajar terhadap Indeks Prestasi Mahasiswa Fakultas Kedokteran - Kevin Chandra; Firginia P. Manoppo; Yanti M. Mewo (Universitas Sam Ratulangi, 2023)
Abstract: In good learning achievement, good learning motivation is needed to encourage students to study. Therefore, learning motivation and learning achievement are interrelated and inseparable. One of the benchmarks in academic achievement is Grade Point Average (GPA). Results of the previous study showed that the Cumulative GPA (CGPA) in developing countries still has the potential to be further improved. This study aimed to find out the role of learning motivation on the CGPA of medical faculty students. This was a literature review study using three databases, namely Pubmed, ClinicalKey, and Google Scholar. The keywords used in the search for articles were